Causality Between Irritable Bowel Syndrome and Suicide Attempt: A Mendelian Randomization Study - Zhen Deng; Kai Wang; Tianshu Hou (Brain and Behavior)
ABSTRACT Background Prior research has indicated a correlation between irritable bowel syndrome (IBS) and suicidal behavior. Nevertheless, it remains uncertain if this correlation implies causation. Methods We used univariate and multivariate Mendelian randomization. The United Kingdom Biobank provided 53,400 European patients and 433,201 European controls for the IBS GWAS. The outcome variable was developed from a genome‐wide association analysis of 26,590 suicide attempt cases and 492,022 controls from the International Suicide Genetics Consortium. BioBank Finland GWAS data (9,771 cases and 402,410 controls) was used for SA validation. Primarily employing inverse variance weighting (IVW), we conducted the analysis to establish causality. MR‐Egger and weighted median were used as complementary methods to reinforce the robustness and validity of the results. We used the MRlap method to eliminate the effect of sample overlap. We also used a multivariable MR approach to control for the influence of potential confounders. Using a number of approaches, including the Cochran's Q test, the MR‐Egger intercept, and the MR‐PRESSO methodology, the study examined pleiotropy and heterogeneity. Results We discovered evidence for an elevated risk of suicide attempt with IBS (OR = 1.67, 95% CI = 1.21–2.35, P = 5.52E–07). MRlap analyses similarly support this result. We got the same results with the validation data (OR = 1.19, 95% CI = 1.06–1.34, P = 2.46E–03). The relationships between the different sensitivity analysis approaches were similar, and there was no indication that outliers influenced these correlations. The independent causal impact of IBS on suicide attempts was maintained after controlling for anxiety, depression, and abdominal pain. In reverse MR, we found no causal link between suicide attempt and IBS. Conclusion Our MR analysis indicates a causal relationship between IBS and suicide risk. Early detection and intervention in suicidal ideation in IBS patients reduces their suicide risk. More study is needed to understand the mechanisms that link IBS and suicidal behavior, which may alter or broaden therapy for specific individuals.